Application research status of high-entropy alloys in welding field - ZHANG Binggang; YU Tao; WANG Houqin; HAN Ke (Journal of Aeronautical Materials, 2022)
Owing to novel design concepts and their unique properties, high-entropy alloy (HEA) has become a hot topic in material science. At present, the studies and applications of high-entropy alloy are still mainly limited to the preparation and synthesis of materials. With its wide application in industry, it must involve the research of high-entropy alloy in welding field. This paper describes the welding of high-entropy alloy with the same material, welding between high-entropy alloy and dissimilar material, and welding between dissimilar material with high-entropy alloy as filler material. The paper focuses on analyzing the welding method, high entropy alloy components, the initial state of welding and welding parameters, and other factors on the joint organization and properties. While the high-entropy alloy is mainly applied as filler material, the high entropy effect and hysteresis diffusion effect for interface controlling are particularly important. Finally, the high-entropy alloy coatings under different preparation methods are analyzed in detail, introducing the cladding process, the addition of microelements, the effect of post-heat treatment, and comparing the wear resistance high-entropy alloy coatings under the laser melting process. By summarizing the research and application of high-entropy alloy in the welding field, it is pointed out that the current problems are that the corresponding standard between high-entropy alloy system and welding process has not been established and the formation mechanism of defects has not been clarified. The future research directions of high entropy alloy in welding field are proposed.